2018
DOI: 10.1111/gcbb.12531
|View full text |Cite
|
Sign up to set email alerts
|

Wild bee diversity is enhanced by experimental removal of timber harvest residue within intensively managed conifer forest

Abstract: The use of timber harvest residue as an energy source is thought to have environmental benefits relative to food‐based crops, yet the ecological impact of this practice remains largely unknown. We assessed whether the abundance and diversity of wild bees (Apoidea) were influenced by the removal of harvest residue and associated soil compaction within managed conifer forest in western Oregon, USA. We sampled bees over two years (2014–2015) on study plots that were subjected to five treatments representing gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…We found that seasonal variation of bee richness in pan traps stayed relatively stable at both higher and lower levels of floral richness compared to bee composition in nets. This may be because pan traps can detect bees regardless of floral resource availability, including when there is a complete absence of vegetation (Rivers et al., 2018), whereas netting relies heavily on the availability of flowers from which the collector can sample (Cane et al., 2000; Gibbs et al., 2017; Nielsen et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that seasonal variation of bee richness in pan traps stayed relatively stable at both higher and lower levels of floral richness compared to bee composition in nets. This may be because pan traps can detect bees regardless of floral resource availability, including when there is a complete absence of vegetation (Rivers et al., 2018), whereas netting relies heavily on the availability of flowers from which the collector can sample (Cane et al., 2000; Gibbs et al., 2017; Nielsen et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of bees in pan traps is often used as a proxy measure of abundance in a given habitat (Rivers et al., 2018) and to estimate community composition (Mallinger et al., 2016; O'Connor et al., 2019; Smith DiCarlo et al., 2020; Westphal et al., 2008). Our work shows that this relationship is complex and that pan traps are potentially problematic for community metrics that rely on abundance measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Given such low capture rates across studies, this approach requires either numerous traps or many days of sampling to yield adequate data. Capture rates appear to vary regionally and among ecosystems, with the highest reported rates (0.62 and 0.27) coming from agricultural areas in California (Sardiñas et al ., 2016a; Sardiñas et al ., 2016b) and the lowest published rates (0.01) coming from harvested forests in Oregon (Rivers et al ., 2018). The rate of capture in this study (0.05) is quite similar to rates (0.04 and 0.05) previously reported from Florida (Cope et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We found that harvesting plantation woody debris correlated with higher bee abundances but on a per-individual basis, and species richness and community evenness were markedly lower. This is perhaps unsurprising, given that coarse woody debris has been associated with wood-nesting bee diversity in other managed forests (Rivers, Mathis, Moldenke, & Betts, 2018;Rodríguez & Kouki, 2017). Physical soil disturbance from the collection of debris may also impact ground nesters (Vázquez, Alvarez, Debandi, Aranibar, & Villagra, 2011).…”
Section: Treatment Of Woody Debrismentioning
confidence: 99%